Penggunaan Suksinilkolin Setelah Tidak Meningkatkan Kadar Kalium Plasma Pasien dengan Cedera Kepala Berat - Purwati, Wahyuni Dian; Wardhani, Viera; Mahameru, Gunung; Istiadjid, Mohamad (Fakultas Kedokteran Universitas Brawijaya, 2009)
This study aimed to identify the changes of plasma potassium level after intubation with rapid sequenceintubation method in severe head injury patients using succinylcholine as muscle relaxant. Subjects aresevere head injury patients with glasgow coma scale (GCS) â‰¤ 8. Plasma potassium level was measured twice,before intubation and (minutes 5, 10, 15, 20) after intubation. Another variable that also measured were bloodgas analyze, time intubated and injury in another organ. There were 34 patients who came to EmergencyDepartment (ED) of Saiful Anwar General Hospital since January until April 2009. Mean level of plasmapotassium changes after intubation minute 5 (-0.01529); minute 10 (-0.01971); minute 15 (0.04147); minute20 (0.00059). Statistical analysis using paired t test revealed no significance of this difference (p>0.05). Therewere no changes of plasma potassium level in severe head injury patients after intubation withsuccinylcholine